Enunciação nas transmissões ao vivo do UOL News no YouTube e os simulacros de reciprocidade - Eltz, Luiza (2024)
The dissertation examines live broadcasts on YouTube, grounded in the interaction, meaning, and risk regimes proposed by Landowski (2014) and the discursive interactions of Oliveira (2013). The justification is based on the growing consumption of journalistic content on this platform and the need to understand how YouTube uses technological tools to bring senders closer to their respective receivers and provide, as stated by the company itself, a sharing of worlds. How do news organizations create their interactions with recipients on this interface? To this end, the research studied the UOL News broadcast, from UOL, one of the most accessed news portals in Brazil, and the last three editions of the webcast transmitted before the second round of elections, on October 28, 2022, a choice guided by the expectation of a rupture in the isotopy constructed during Bolsonaro’s Government. YouTube proposes an experience aimed at a logic of sociability in which the subject seeks to acquire the necessary competencies to enjoy being together with others. Therefore, it is a loyal user who consumes videos in which they feel like an author-sender within a community. In live broadcasts, this is highlighted by the use of live chat, which strengthens a simulacrum of reciprocal enunciation. In the case of the UOL News product, this Sender uses the social network to indicate to the subject that they are as much an interlocutor as those in front of the cameras, a crucial part of the webjournal’s enunciation. In the analyzed segment, UOL News demonstrated, through discursivization, that the construction of a sense of reciprocity was fundamental to strengthening the bond with the community and stimulating the prescriptive nature of interpretative actions concerning the political views presented. The research argues that the reason for this conduct is partly justified by a UOL Sender who tries to secure its authority to inform in the digital world; and by the fact that YouTube demands that the performance be carried out following certain prescriptions. Therefore, the simulacrum of belonging conferred on the recipient is essential for journalism to gain notoriety, a trajectory that begins to unite in "social bubbles" communities seeking to find the other and themselves